Identity, ideology, and capital in EFL learning: a narrative case study - Adilur Rahaman (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract Research on learners’ commitment to English language learning in the field of second language acquisition (SLA) around the world is predominantly characterized by a positivist and quantitative approach. Conventionally, this type of studies uses the psychological construct ‘motivation’ to account for learners’ efforts in language learning practices. Such paradigmatic orientation constituted a knowledge gap on the role of society, structural inequality, and uneven distribution of resources in English language learning. To address this gap, with a poststructuralist approach, this paper reports on an in-depth narrative case study of an underprivileged learner’s engagement in English language learning in Bangladesh through Darvin and Norton's (Ann Rev Appl Linguist 35: 36–56, 2015) expanded model of ‘investment’, a sociological counterpart of the psychological theory of ‘motivation’. Data for the study were collected over a two-year period through narrative interviews, a written autobiography, and informal conversations. The collected data were analyzed deductively following Polkinghorne's (Int J Qual Stud Educ 8: 5–23 1995) ‘analysis of narrative’ approach in connection with the expanded model of ‘investment’ which focuses on identity, ideology, and capital. In particular, findings demonstrate that (a) imagined identity and group membership influence commitment to language learning; (b) ideologies embedded in language education policy, linguistic gatekeeping, and methodologies of English language teaching configure language learning practices; and (c) the fluid nature of the three forms of capital (i.e., economic, social, and cultural) enables the participant to engage in learning English. The findings of this study have implications for language educators and second language acquisition (SLA) researchers.